RECUPERACION FUNCIONAL DE PACIENTE CON TUMOR MAXILAR SUPERIOR E INVASION DE MUSCULATURA PTERIGOIDEA - Sandoval Igelmo, Blanca (Revista ORL, 2018)
ABSTRACT INTRODUCTION Adenoid cystic Carcinoma (CAQ) is a salivary glands tumor with a biological behavior characterized by a high rate of local recurrences and a rate of metstases between 40% and 60%. It accounts for 30% of facial tumors. The treatment consists of surgery, chemotherapy and radiotherapy. Itusually causes important sequelae such as swallowing disfunction, dysartria and temporomandibular joint ankylosis. CLINICAL CASE An adenoid cystic tumor that invaded the locallypterygoid musculature with a perineural extension was diagnosed in a 27-years-old patient in may 2016. As the patient is a musician, he plays the horn, he was treated by the Medicine of the Musicians Healthcare Service. The patient presented a partial resection of the maxilar added with an extensive exeresis of palatal veil. The tumor treatment included chemioteraphy and radiotherapy with a successfull result and a complete illness remission. PHYSICAL EVALUATION Once completed the chemioteraphy and radiotherapy treatment, the phyisical evaluation determined some sequlae such as swallowing disfunction and a maxilar anquilosis with limited mouth opening. The patient treatment consisted of physiotherapy and speech therapy with the objetive of recovering swallowing and speech function In adtition, the pacient followed a training program of respiratory exercises. EVOLUTION After the traitment, we observeda complete recovery of swallowing and speech functions despite the patient was not able, at that moment, to play the horn because of a lack of structure in his palatal veil caused by the surgery. DISCUSSION In cases of extensive resection of the oral cavity, the sequelae are usually oropharyngeal dysphagia and speech disfunction. They can be avoided by using speech therapy and phisiotherapy treatments. Key words: Adenoid cystic Carcinoma, Rehabilitation, Speech Therapy